Geometric Constraints and Anti-overturning Capability of a Reconfigurable Quadruped Mobile Robot - Chao Chai; Ruiqin Li (Jixie chuandong)
Aiming at unmanned regions such as mine and space，a quadruped parallel mobile robot with self-recovery ability after overturning is presented. The leg structure of the quadruped robot is composed of a reconfigurable spatial six-bar mechanism，which consists of two improved spherical five-bar mechanisms connected in parallel and has two different motion configurations，the motion configuration I has three degrees of freedom （1R2T），which satisfies the degrees of freedom requirements of the leg walking mechanism for the quadruped robot，and the motion configuration II has two degrees of freedom and a larger workspace，which satisfies the workspace conditions needed for the robot to rolling over. Based on screw theory，the geometric constraints of the spherical five-bar mechanism and the reconfigurable six-bar mechanism are analyzed. These two motion configurations have the interlocking performance. The inverse kinematics of the reconfigurable six-bar mechanism is analyzed using D-H method，and the workspace is obtained. The realizability of the robot rolling over is verified. The rolling over gait of the quadruped robot is analyzed. The relationship between the rotation angles of the leg motors and the center of gravity of the robot body is obtained when the quadruped robot recovers itself after overturning. During the rolling over process of the quadruped robot，the reconfigurable six-bar mechanisms of its legs are all in the motion configuration II. The dynamic model of the quadruped robot is established to verify the correctness and rationality of the preset rolling over gait.